Samuel Johnson and the making of modern England - Hudson, Nicholas (Cambridge University Press, 2003)
One of the most renowned authors of the eighteenth century, Samuel Johnson became a symbol of English national identity in the century following his death in 1784. Nicholas Hudson examines his contribution to the creation of the modern English identity, focusing on his attitudes towards class, feminism, party politics, the public sphere, nationalism, and imperialism. This new view of Johnson reflects the nature of English nationhood